Modern Fiqh Paradigm in Indonesia: a Study of Nurcholish Majid’s Though - Moh Dahlan, M. Ag. (Archives of Business Research, 2019)
Islam as a rahmatan lil Alamin (mercy to the entire universe) religion, basically, has the passion to drive the dynamics of the human race, but in fact, it still has not reached ideal expectations because of the assumption about the door ijtihad is closed, taklid attitude, heresy and superstition, as well as textual classic ijtihad paradigm. Based on this explanation, problem formulations were stated as follows: how is the modern fiqh ijtihad paradigm built by Madjid? How is the modern fiqh ijtihad paradigm built by Madjid in Indonesia? The study used the theory of paradigm shift by Thomas S. Kuhn and theory maqasid al-shari'ah. The results of this study indicated that there was a paradigm shift from the ijtihad classical paradigm to the modern ijtihad paradigm built based on muhkamat passages, not mutashabihat passages. The paradigm shift purposes built by Madjid is to ensure the maintenance of the five principles of law construction, they are (a) maintaining religion as a means to realize the depth of faith and righteous deeds; (B) maintaining thought to realize the usage of the mind and the dynamics of science; (C) maintaining the soul in the sense of respecting and keeping the existence of human rights and fundamental freedoms; (D) maintaining the honor as a means to embody the values of equality, personal and collective dignity, and avoiding any kind of cult of other than Allah; and (e) maintaining the property as a means to maintain economic stability and equal distribution of wealth in life in Indonesia.